HUBUNGAN LAMA MENDERITA DENGAN TINGKAT STRES PADA PENDERITA TUBERKULOSIS PARU DI PUSKESMAS PEKAUMAN BANJARMASIN - Nurjihan, Nabila; Heriyani, Farida; Al Audhah, Nelly; Haryati, Haryati; Skripsiana, Nika Sterina (Universitas Lambung Mangkurat, 2024)
Abstract: Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Suffering Pulmonary TB treatment takes a long time and must be routine for at least 6 months. This research method is analytical observational with a cross sectional approach. The sample was selected using a purposive sampling technique with 42 samples. Data was collected by interviewing the length of time suffering from pulmonary tuberculosis and to determine stress levels. The data was analyzed using the chi square test with a confidence level of 95%. From the research results, it was found that 24 samples suffered from pulmonary tuberculosis for >2 months and 18 samples suffered from pulmonary tuberculosis for ≤2 months, while for severe-very severe stress levels there were 16 samples, 13 samples for mild-moderate stress levels and 13 samples for normal stress levels. The static test results obtained a p value = 0.001. The conclusion of this research is that there is a relationship between the length of suffering and the level of stress in pulmonary tuberculosis sufferers at the Puskesmas Pekauman Banjarmasin. Keywords : Pulmonary Tuberculosis, Long Term Suffering, Stress Level, DASS 42 (Depression, Anxiety, and Stress Scales), Puskesmas Pekauman Banjarmasin. Abstrak: Tuberkulosis paru adalah penyakit infeksi yang disebabkan oleh bakteri Mycobacterium tuberculosis. Pengobatan TB paru memerlukan waktu lama dan harus rutin minimal 6 bulan. Metode penelitian ini adalah observasional analitik dengan pendekatan cross sectional. Sampel dipilih dengan menggunakan teknik purposive sampling dengan 42 sampel. Data dikumpulkan dengan cara wawancara untuk menentukan lama menderita tuberkulosis paru dan menentukan tingkat stres. Data dianalisis menggunakan uji chi square dengan tingkat kepercayaan 95%. Hasil penelitian, mendapatkan 24 sampel menderita tuberkulosis paru >2 bulan dan 18 sampel menderita tuberkulosis paru ≤2 bulan, sedangkan untuk tingkat stress, berat-sangat berat terdapat 16 sampel, tingkat stres ringan-sedang 13 sampel dan normal 13 sampel. Hasil uji statik didapatkan nilai p = 0,001. Kesimpulan penelitian ini terdapat hubungan antara lama menderita dengan tingkat stres pada penderita tuberkulosis paru di Puskesmas Pekauman Banjarmasin. Kata-kata kunci : Tuberkulosis Paru, Lama Menderita, Tingkat Stres, Puskesmas Pekauman Banjarmasin